Street art conservation: The drift of abandonment - Gayo, Elena García (Street Art & Urban Creativity, 2015)
There is a need to create a documentation system adapted to facilitate the conservation and restoration of Street Art and Graffiti. Even though they are ephemeral manifestations of art, there have been some signs of the need for preservation mechanisms that would respect their own special features. For selected works we must establish a procedure that enables their preservation with the highest guarantee.